2017
DOI: 10.1002/joec.12060
|View full text |Cite
|
Sign up to set email alerts
|

“Give Us a Chance”: Understanding Job Seeking Among Women Experiencing Homelessness

Abstract: The purpose of this phenomenological study was to explore perceptions of job seeking from women experiencing homelessness. Participants (N = 9) were interviewed at a transitional housing facility in North Florida. Thematic analysis found several manifest and latent themes related to stigma, barriers, and perseverance. The findings of this study support the existing literature on the management of social stigma by people experiencing homelessness. It also provides new findings that allow for a more nuanced unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Rayburn and Guittar (2013) also demonstrated the association of homelessness stigma and parental stress. Furthermore, Groton et al (2017) found that potential employers' stigma against homeless individuals may have prevented said individuals from getting a job.…”
Section: Homelessness Stigma and Caregiver Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Rayburn and Guittar (2013) also demonstrated the association of homelessness stigma and parental stress. Furthermore, Groton et al (2017) found that potential employers' stigma against homeless individuals may have prevented said individuals from getting a job.…”
Section: Homelessness Stigma and Caregiver Stressmentioning
confidence: 99%
“…Another stressor that caregivers face is homelessness stigma (Bradley et al, 2018; Groton et al, 2017; Rayburn & Guittar, 2013). Discrimination is an emotional experience as in personal attachment insecurity, but it mostly comes from strangers.…”
Section: Relevance Of Attachment Theory and Abc‐x Model To Homelessnessmentioning
confidence: 99%